The Influence of Price and Service Quality on Customer Loyalty at Riska Laundry Palembang - Salsabila, Nabila; Rosa, Aslamia; Yunita, Dessy (Majapahit Journal of Islamic Finance and Management, 2025)
The laundry service sector in Indonesia is rapidly growing due to increasingly busy lifestyles and heightened competition, which motivates this study to analyze the impact of price and service quality on customer loyalty at Riska Laundry Palembang. The objective of this study is to examine the extent to which price and service quality factors influence customer loyalty among users of Riska Laundry Palembang. This research employs two types of data: primary and secondary data. The sample was selected using non-probability sampling with a purposive sampling approach, totaling 90 respondents. The analytical technique applied in this study is multiple linear regression, utilizing SPSS Statistics 27 for Windows. The results of the t-test and F-test demonstrate that both price and service quality factors have a positive and significant effect on customer loyalty, both individually and simultaneously, among customers of Riska Laundry Palembang.